2023
DOI: 10.1371/journal.pgen.1010500
|View full text |Cite
|
Sign up to set email alerts
|

An atypical NLR protein modulates the NRC immune receptor network in Nicotiana benthamiana

Abstract: The NRC immune receptor network has evolved in asterid plants from a pair of linked genes into a genetically dispersed and phylogenetically structured network of sensor and helper NLR (nucleotide-binding domain and leucine-rich repeat-containing) proteins. In some species, such as the model plant Nicotiana benthamiana and other Solanaceae, the NRC (NLR-REQUIRED FOR CELL DEATH) network forms up to half of the NLRome, and NRCs are scattered throughout the genome in gene clusters of varying complexities. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 91 publications
(175 reference statements)
1
25
0
Order By: Relevance
“…1a). Six NLRs were excluded from the library due to short amino acid sequences, high sequence similarities with other NLRs in the same phylogenetic groups, or retardation of growth postsilencing (Table S1; Adachi et al ., 2023). The NbNLR VIGS constructs were labeled from Com‐1 to Com‐55 and transformed to A. tumefaciens for VIGS.…”
Section: Resultsmentioning
confidence: 99%
“…1a). Six NLRs were excluded from the library due to short amino acid sequences, high sequence similarities with other NLRs in the same phylogenetic groups, or retardation of growth postsilencing (Table S1; Adachi et al ., 2023). The NbNLR VIGS constructs were labeled from Com‐1 to Com‐55 and transformed to A. tumefaciens for VIGS.…”
Section: Resultsmentioning
confidence: 99%
“…NRC4 (Adachi et al, 2023a). This points to NRCX as an immunomodulating component in the NRC network, specifically capable of regulating the functions of NRC2 and NRC3 (Fig 3).…”
Section: Cell Biology Of Nlr Resistosomesmentioning
confidence: 84%
“…NLRs, especially TIR-type NLRs, can show induced expression during pathogen infection, thereby enhancing general immunity or priming the immune system (Mohr et al, 2010;Yu et al, 2013;Tian et al, 2021). Similarly, Adachi et al (2023a) reported that some NRC helper genes are induced following pathogen infection. NRC2a and NRC2b were upregulated following treatment of N. benthamiana leaves with the nonpathogenic Pseudomonas fluorescens, while other NRC genes such as NRC3 and NRC4a/b and the immunomodulator NRCx remained unchanged.…”
Section: Tissue and Cell Specificity Of Nlr Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…NRC0 often exists in a gene cluster with NRC0-dependent sensor NLRs, strengthening the hypothesis that the NRC superclade originated from an ancient helper-sensor NLR gene cluster (Wu and Kamoun, 2021). Another intriguing evolutionary aspect of the NRC superclade is the presence of noncanonical extended N-terminal domains (exNT), which exist before the CC domain in some clades of sensor NLRs (Seong et al, 2020; Adachi et al, 2023a). Although the detailed evolutionary history of the sensor NLRs is not clear, the exNT were also found in sugar beet, suggesting that the exNT of NRC-dependent sensor NLRs emerged between the common ancestor of asterids and Amaranthaceae (Caryophyllales) (Seong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%